Ahkam iltizam al- Daman fi al-Hibah; Dirasah Fiqhiyyah Muqaranah - Abdul waly assulamy (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2017)
The study aimed to find out the rule of security commitment to the donation in Islamic jurisprudence, has followed the inductive and analytical and descriptive writing research, was a statement of what the gift in the language and terminology, as well as the fact that commitment, and security, as well as the statement of the rule of security commitment to the donation, through the display the views of scholars and their evidence and out opinion the most correct, and the study showed a number of results mainly because of his talented on the donor in the event of the appearance of a defect in the gifted thing, if the gift aegypti, Vestrd Awad if it exists, but if the damage, the donor is committed to guarantee the talented, and commitment The guarantee shall be like that if it is Its like, otherwise A value and recommended study care of the subject of the rule of security commitment in the donation through seminars and television programs, and teaching at universities